Influence of combined non-uniform wire coil and twisted tape inserts on thermal performance characteristics - Eiamsa-ard, S.; Nivesrangsan, P.; Chokphoemphun, S.; Promvonge, P. (My University, 2010)
In this paper, heat transfer, friction factor and thermal performance behaviors in a tube equipped with the combined devices between the twisted tape (TT) and constant/periodically varying wire coil pitch ratio are experimentally investigated. The periodically varying three coil pitch ratios were arranged into two different forms: (1) D-coil (decreasing coil pitch ratio arrangement) and (2) DI-coil (decreasing/increasing coil pitch ratio arrangement) while the twisted tapes were prepared with two different twist ratios. Each device alone is also tested and the results are subjected for comparison with those from the combined devices. The experiments were conducted in a turbulent flow regime with Reynolds numbers ranging from 4600 to 20,000 using air as the test fluid. Compared to each enhancement device, the heat transfer rate is further augmented by the compound devices. Over the range investigated, the highest thermal performance factor of around 1.25 is found by using DI-coil in common with the TT at lower Reynolds number. In addition, the empirical correlations of the heat transfer (Nu) and pressure drop (f) are also presented. © 2010 Elsevier Ltd.
Keywords: Heat transfer enhancement; Twisted tape; Variable/non-uniform wire coil; Wire coil